Divergent Thinking and Evaluative Skill: A Meta‐Analysis. (23rd February 2022) - Guo, Yawei; Lin, Shengjie; Acar, Selcuk; Jin, Shuxian; Xu, Xizheng; Feng, Ye; Zeng, Yuntao
Abstract: Evaluative skill, the ability to accurately assess ideas in terms of originality or creativity, is a critical component of creativity. It involves discarding bad ideas and discerning ideas that are worthwhile to pursue. In light of the growing research on the association between individuals' evaluative skill and divergent thinking (DT), a research synthesis is needed to clarify discrepant results. Therefore, we examined the relationship between DT and evaluative skill with a three‐level meta‐analytic approach. Based on 96 effect sizes in 20 studies with a total sample of 3, 019 participants, results indicated that DT was positively associated with evaluative skill, r = .13 (95% CI [.07, .20], p < .001). Follow‐up moderator analyses revealed that the type of DT tests, the source of ideas, and the type of evaluation tasks were significant moderators. Compared with Instances, Line Meanings, and Consequences, the relationship was (a) weaker when the Uses task was used as the DT test, (b) stronger when the evaluation task was based on Uses, and (c) stronger when people rated their own ideas than when they rated others. The findings implied that DT and evaluative skill are conceptually distinct but interrelated and suggested ways to enhance evaluative skill.